Eccentric Exercise Leads to Glial Activation but not Apoptosis in Mice Spinal Cords - Pereira, B. C.; Lucas, G.; da Rocha, A. L.; Pauli, J. R.; Ropelle, E. R.; Cintra, D.; de Souza, C. T.; Bueno, C. R.; da Silva, A. S. (International Journal of Sports Medicine, 2015)
The aim of this investigation was to evaluate the effects of 3 overtraining (OT) protocols on the glial activation and apoptosis in the spinal cords of mice. Rodents were divided into control (C; sedentary mice), overtrained by downhill running (OTR/down), overtrained by uphill running (OTR/up) and overtrained by running without inclination (OTR). The incremental load test, ambulation test, exhaustive test and functional behavioural assessment were used as performance evaluation parameters. 36 h after the exhaustive test, the dorsal and ventral parts of the lumbar spinal cord (L4-L6) were dissected for subsequent protein analysis by immunoblotting. The OT protocols led to similar responses of some performance parameters. The ventral glial fibrillary acidic protein (GFAP) protein levels were diminished in the OTR/up and OTR compared to CT and OTR/down groups. The ventral ionized calcium binding adaptor molecule 1 (Iba-1), and the dorsal GFAP and Iba-1 protein levels were increased in the OTR/down compared to the other groups. The ratio between the cleaved capase-3/caspase-3 and cleaved caspase-9/caspase-9 measured in the spinal cord were not sensitive to the OT protocols. In summary, the OTR/down activated the glial cells in the motor (i. e. Iba-1) and sensory (i. e. GFAP and Iba-1) neurons without leading to apoptosis.
Keywords: overtraining protocols; spinal cord; glial activation; apoptosis; mice